(untitled) (Studia austriaca, 2020)
Recent studies on German literature have highlighted a trend towards recovering the registers of realism. Previously discredited notions of literary theory have also been reconsidered, primarily that of character. In view of this, this work focuses on the strategies of writing and the features of the character in some selected novels from Peter Handke’s early production. It is shown how the experimental tendency of the author weakened in the ’70s, especially when Handke came to write about his mother’s suicide in Wunschloses Unglück. In order to make sense of such a loss, the writer is led to reconsider a tradition he had theoretically criticized and practically liquidated, though without abandoning entirely the aesthetic principles which had shaped his first works.